Al-Raniri’s discourse on cleanliness and religions other than Islam - Abdul Jalil, Mohd Noh (2021)
This article discusses discourse on cleanliness and its relationship with religions other than Islam by Al-Raniri in his 17th century classical Malay text, ØirÉÏ al-MustaqÊm. Discourse on religions other than Islam is not common in classical Malay texts. Most religious texts at that time were focusing more on the fundamental teachings of Islam such as aqidah, fiqh, tafsir, akhlaq to name a few. There is no single text which discusses entirely on religions other than Islam. Despite the inavailibity of such text at that time, the discourse on religions other than Islam still exist. A Muslim scholar, Nur al-Din al-Raniri continued the discourse even the subject matter of his text is not on other religions. The ability by al-Raniri to bring in the discourse on religions other than Islam while discussing other issues such as cleanliness in Islam is exceptional and requires indepth study. His text on cleanliness ØirÉÏ al-MustaqÊm includes religions other than Islam such as Christianity and Hinduism. A thorough study on this text reveals a bigger picture about the context as well as the author’s struggle to bring the understanding of Islam to the local people. He did not miss any chance to educate the Muslims about the threats posed by other religions even while discussing about the issues of cleanliness.